2009
DOI: 10.1002/eji.200839098
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of survivin‐derived H‐2Kb‐restricted CTL epitopes

Abstract: Survivin is overexpressed in several malignancies and in tumor-associated endothelium making it an attractive target for therapeutic cytotoxic T-cell responses. Thus, it would be important to test this notion in preclinical models. Consequently, we screened the murine survivin sequence for potential binding K b -restricted octamer peptide epitopes. Two epitopes, which bind strongly to K b , were selected to test their immunogenicity in vivo.Spleen cells from mice vaccinated by intradermal injection of mature D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…However, it is not clear which will bring about a better antitumor effect: targeting CSC antigens or targeting shared antigens. On the basis of this point of view, we compared the immunogenicity of DNAJB8 with that of the well-characterized TAA Survivin (26)(27)(28)(29), as Survivin is expressed in both CSCs/ CICs and non-CSCs/CICs at the same levels (Fig. 5A) and it is a shared antigen.…”
Section: Dnajb8-targeting Immunotherapymentioning
confidence: 99%
“…However, it is not clear which will bring about a better antitumor effect: targeting CSC antigens or targeting shared antigens. On the basis of this point of view, we compared the immunogenicity of DNAJB8 with that of the well-characterized TAA Survivin (26)(27)(28)(29), as Survivin is expressed in both CSCs/ CICs and non-CSCs/CICs at the same levels (Fig. 5A) and it is a shared antigen.…”
Section: Dnajb8-targeting Immunotherapymentioning
confidence: 99%
“…As outlined in this review, (i) the involvement of survivin in multiple cellular networks, (ii) its over‐expression which is almost completely restricted to malignant tissues, (iii) the observations that survivin may confer resistance to anti‐cancer therapy and (iv) the role that survivin might play in tumour initiation and/or progression in angiogenesis, make this protein an attractive target for cancer therapy. In skin, most of the anti‐survivin therapeutic strategies have been applied so far for cutaneous melanoma in preclinical animal models (136) as well as clinical trials (3,126,127,137).…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
“…4D, Western blot). A study recently identified a survivin-derived H-2K b -restricted CTL epitopes that could inhibit tumor growth in mouse model (17). We used the survivin-derived peptides as stimulator to activate survivin-specific T-cell population in the splenocytes in ELISpot assay.…”
Section: Targeted Gene Therapy Elicits Cancer-specific Immune Responsementioning
confidence: 99%